2017
DOI: 10.1371/journal.pone.0169760
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Changes in the CacyBP/SIP Interacting Protein S100A6 in the Mouse Brain

Abstract: The CacyBP/SIP target S100A6 is widely present in the nervous system, and its up-regulation is associated with certain neurodegenerative diseases. Here, we examined the involvement of S100A6 protein in stress responses in mice. Using Western blotting, we observed a marked change in brainstem structures, whereby stressed mice showed approximately one-third the protein level produced in the control group. A decreased level of S100A6 protein in stressed animals was also detected in the olfactory bulb and the cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…These proteins are more represented in IPD line. In common to IPD and GS lines, prothymosin α (Qi et al, 2010 ) and protein S100-A6 (Bartkowska et al, 2017 ) are, respectively, anti-apoptotic and stress modulator. α-Enolase is found in RG line whereas annexin A2 is in all PD models.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are more represented in IPD line. In common to IPD and GS lines, prothymosin α (Qi et al, 2010 ) and protein S100-A6 (Bartkowska et al, 2017 ) are, respectively, anti-apoptotic and stress modulator. α-Enolase is found in RG line whereas annexin A2 is in all PD models.…”
Section: Discussionmentioning
confidence: 99%
“…76 In the mouse brain, the level of S100A6 decreases in response to chronic mild stress, suggesting that this protein may modify stress responses. 77 are involved in carbohydrate/glucose metabolism. 87 The differences in glucose level were observed between strains of tame and aggressive rats (Rattus norvegicus) with higher glucose levels in the blood of aggressive rats.…”
Section: F I G U R Ementioning
confidence: 99%
“…Particularly, the protein was found in pyramidal neurons of the hippocampus and cortex, granule cells in the cerebellum, neurons in the brain stem, in olfactory receptor cells, astrocytes in white matter, some ependymal cells (especially around the central canal), and in Schwann cells. Other studies performed on mouse brain showed high expression of S100A6 in astrocytes localized in the border zones of all brain ventricles, tanycytes of the hypothalamus, and neurons of the olfactory bulb, hippocampus, thalamus, cerebral cortex, brainstem, and cerebellum [18,19]. Interestingly, an increase in S100A6 reactivity in astrocytes of the mouse hippocampus was observed in aged animals [20].…”
Section: Expression Of S100a6 In the Brainmentioning
confidence: 84%
“…In the SGZ, high S100A6 expression was observed in quiescent NSCs and in lineage-restricted astrocyte precursors but only rarely in neural-lineage precursors [22]. The presence of S100A6 in the progenitor cells in SGZ was later confirmed by co-immunostaining with transcription factor, SOX2 [18]. In SEZ, S100A6 staining extended to the rostral migratory stream and was observed in NSCs but not in doublecortin-positive neuroblasts [23].…”
Section: Expression Of S100a6 In the Brainmentioning
confidence: 92%